2010
DOI: 10.1088/0143-0807/31/2/015
|View full text |Cite
|
Sign up to set email alerts
|

Studying the physical basis of global warming: thermal effects of the interaction between radiation and matter and greenhouse effect

Abstract: We present a teaching module dealing with the thermal effects of interaction between radiation and matter, the infrared emission of bodies and the greenhouse effect devoted to university level and teacher education. The module stresses the dependence of the optical properties of materials (transparency, absorptivity and emissivity) on radiation frequency, as a result of interaction between matter and radiation. Multiple experiences are suggested to favour a progressive construction of knowledge on the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
0
28
0
2
Order By: Relevance
“…Some difficulties about these aspects were expected from previous studies concerning the multiplicative aspect (Viennot, L. & de Hosson 2012) and the transition between a transient and a steady state (Viennot, L., 2001;Colin, 2011;Besson et al, 2010). Sub categories (see Table 3) were deduced from our content analysis, which may involve complex frameworks.…”
Section: Conceptual Aspectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some difficulties about these aspects were expected from previous studies concerning the multiplicative aspect (Viennot, L. & de Hosson 2012) and the transition between a transient and a steady state (Viennot, L., 2001;Colin, 2011;Besson et al, 2010). Sub categories (see Table 3) were deduced from our content analysis, which may involve complex frameworks.…”
Section: Conceptual Aspectsmentioning
confidence: 97%
“…As far as we are concerned, we choose to focus on common ways of reasoning that can be observed in different physical contexts. Such is the case of linear causal reasoning (Fauconnet 1984, Driver et al 1985, Rozier and Viennot, L. 1991, Viennot, L. 1988, 2001 currently observed in the analysis of systemic situations (Colin 2011, Besson et al 2010. We also pay special attention to students' preference for an additive or subtractive approach to a phenomenon rather than for a multiplicative approach de Hosson, 2012, 2015).…”
Section: Rationalementioning
confidence: 99%
“…More specifically, research has revealed the following issues (Besson, De Ambrosis, & Mascheretti, 2010;: (i) infrared emission of bodies is usually not taken into account as an energy-loss mechanism, (ii) emittance, when considered, is often confused with reflectance, (iii) students tend to give absolute meaning to properties like transparency, absorptivity and emissivity, rather than seeing them as interactive properties, (iv) radiation is often confused with heat, and (v) students tend to apply a temporal or linear causal reasoning (Rozier & Viennot, 1991) for explaining processes instead of causal schemes based on balancing and equilibration (diSessa, 2014). These tendencies lead students to interpret the greenhouse effect with the naïf metaphor of "trapping" (Besson et al, 2010) which is not only misleading but also ineffective for grasping concepts such as feedback. The known difficulties are not surprising since the crucial physics concepts involved in understanding the greenhouse effect (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The known difficulties are not surprising since the crucial physics concepts involved in understanding the greenhouse effect (e.g. transparency) are often treated superficially, both in textbooks and by teachers (Besson et al, 2010). Furthermore, the traditional organization of scientific content in theories could in itself be responsible for creating barriers in understanding the greenhouse effect, considering that this is clearly an intra-disciplinary issue .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation